ON L–FUZZY TOPOLOGICAL TM–SUBSYSTEM - Annalakshmi, M.; Chandramouleeswaran, M. (Italian Journal of Pure and Applied Mathematics, 2014)
Recently, in 2010, Tamilarasi and Megalai introduced a new class of algebras known as TM-algebras. In this paper, we discuss the notion of an L-fuzzy topological TM-subsystem.